2013
DOI: 10.1071/an12345
|View full text |Cite
|
Sign up to set email alerts
|

Egg quality and age of laying hens: implications for product safety

Abstract: Abstract. Eggs were collected from commercial caged layer flocks in early, mid, late and very late lay. Eggs were candled and scored for translucency. Cuticle cover was estimated using MST Cuticle Stain and a Konica Minolta hand-held spectrophotometer. Traditional measures of egg quality were determined using specialised equipment. Shell ultrastructural features were scored following plasma ashing of shell samples and viewing under a benchtop scanning electron microscope. Translucency score was significantly h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
26
3
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 29 publications
5
26
3
3
Order By: Relevance
“…For a*, green is towards the negative end of the scale and red towards the positive end. For b*, blue is towards the negative end and yellow towards the positive end of the scale (Roberts et al 2013). The reading was taken 3 times per location at 3 locations around the equator of each egg and an average was recorded.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For a*, green is towards the negative end of the scale and red towards the positive end. For b*, blue is towards the negative end and yellow towards the positive end of the scale (Roberts et al 2013). The reading was taken 3 times per location at 3 locations around the equator of each egg and an average was recorded.…”
Section: Methodsmentioning
confidence: 99%
“…Totally 330 eggs were used for cuticle estimation by the method of Roberts et al (2013). Eggshells were individually soaked in a MST cuticle blue stain (MST Technologies Ltd., UK) for 1 min and rinsed in tap water 3 times to remove the excess stain.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have shown an increased tendency for flocks to be identified as Salmonella positive as the birds become older (Garber et al, 2003;van de Giessen et al, 2006;Wales et al, 2007;Bouzidi et al, 2012;Roberts et al, 2013) especially if birds have been moulted (Golden et al, 2008) In most cases, the initial infection resulted from residual contamination of laying houses that spread to pullets that are suffering from transport, handling and relocation/remixing stress at a time when hormonal changes associated with the onset of lay are also increasing susceptibility to infection (Line et al, 1997). This leads to a typical early peak of infection within three weeks of housing (Humbert et al, 1995;Gradel et al, 2002) but laying flocks are rarely sampled at this time (16-19 weeks of age).…”
Section: Factors Influencing Detection Of Salmonella Infected Flocksmentioning
confidence: 99%
“…In reflectometer method egg shell color measures and expresses as a percentage of black and pure white, where black refers 0% and the pure white as 100% (Roberts et al, 2013). …”
Section: External Parametersmentioning
confidence: 99%